2016
DOI: 10.1093/mnras/stw284
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced X-ray emission from Lyman break analogues and a possibleLX–SFR–metallicity plane

Abstract: The source of energetic photons that heated and reionized the early Universe remains uncertain. Early galaxies had low metallicity and recent population synthesis calculations suggest that the number and luminosity of high-mass X-ray binaries are enhanced in star-forming galaxies with low metallicity, offering a potentially important and previously overlooked source of heating and reionization. Lyman break analogue (LBA) galaxies are local galaxies that strongly resemble the high-redshift, star-forming Lyman B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
222
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(250 citation statements)
references
References 51 publications
26
222
2
Order By: Relevance
“…X-ray binaries (XRBs) have been suggested as one such mechanism for several decades now (see Garnett et al 1991, for example). Schaerer et al (2019) showed that XRB populations in low metallicity galaxies can account for the He ii line strength, and Fornasini et al (2019) recently showed that the contribution from XRBs indeed increases with decreasing metallicities at high redshifts, as was already shown for low redshift galaxies (Douna et al 2015;Brorby et al 2016). Therefore, it is necessary to explore the role of XRBs in low-metallicity, He ii emitting galaxies with significant enough statistics.…”
Section: X-ray Binariesmentioning
confidence: 93%
“…X-ray binaries (XRBs) have been suggested as one such mechanism for several decades now (see Garnett et al 1991, for example). Schaerer et al (2019) showed that XRB populations in low metallicity galaxies can account for the He ii line strength, and Fornasini et al (2019) recently showed that the contribution from XRBs indeed increases with decreasing metallicities at high redshifts, as was already shown for low redshift galaxies (Douna et al 2015;Brorby et al 2016). Therefore, it is necessary to explore the role of XRBs in low-metallicity, He ii emitting galaxies with significant enough statistics.…”
Section: X-ray Binariesmentioning
confidence: 93%
“…However, the metallicity dependence of BH-HMXBs has been observationally confirmed for galaxies in the local universe 78,79,80 . Using a large set of data on the sizes and X-ray luminosities (mostly coming from accreting BHs) of HMXBs in nearby galaxies with known metallicities and star formation rates, it is found that HMXBs are typically ten times more numerous per unit star formation in low-metallicity galaxies (<20% solar) than in solar-metallicity galaxies 80 .…”
Section: Bh Formation As a Function Of Metallicity And Redshiftmentioning
confidence: 99%
“…We conclude that the age of the IC 10 starburst is fortuitously such that massive binary interaction is approaching its peak. The picture painted in Prestwich et al (2015) and Brorby et al (2016) advances the hope that the observable parameters can be organized into a "fundamental plane" in SFR, XLF, and metalicity. Populating such a plane requires deep multiwavelength observations of star forming galaxies across age and metalicity space and IC 10 is the youngest and most accessible case study.…”
Section: Discussionmentioning
confidence: 99%